Smart Biocomposite Materials : Fabrication, Applications and Sustainability - Md. Rezaur, Rahman (Woodhead Publishing / Elsevier Ltd., 2025)
Smart Biocomposite Materials: Fabrication, Applications and Sustainability presents the latest advancements in this important research field. The book offers comprehensive insights into the classification, innovative fabrication techniques, and functional fillers of biocomposite materials. Additionally, it addresses mechanical performance, environmental impact, bio-sustainability, high-performance applications, and practical implementation. This resource is essential for professionals seeking to adopt sustainable materials in future research projects. Beyond the technical aspects, the book also examines ethical, cultural, and societal factors, providing a holistic view of biocomposite materials. It outlines key challenges and future directions while offering in-depth technical insights to aid informed decision-making.